Staging the sex wars : contemporary American playwrights through the prism of feminist conflict - Hanworth, Cynthia (Department of English Language and Literature, 2016)
This thesis explores various aspects of contemporary American drama by women. The study is facilitated by examining one work by each of seven playwrights and two performance artists who have transcribed their work, namely, Miriam's Flowers by Migdalia Cruz, Abundance by Beth Henley, Bitter Cane by Genny Lim, Traveler in the Dark by Marsha Norman, The Death of the Last BlackMan in the Whole Entire World by Suzan-Lori Parks, spell # 7 by Ntozake Shange, The Sisters Rosensweig by Wendy Wasserstein, The Constant State of Desire by Karen Finley, and World Without End by Holly Hughes. The works chosen, first performed between 1976 (spell #7) and 1992 (The Sisters Rosensweig), include an array of the vast variety of work being done in contemporary theatre. All of the writers are still living and actively working and were selected to provide a sampling of women from the various subcultures in the United States. Neither the works nor the writers are meant to be inclusive or representational of the diversity of American theatre. The thesis briefly discusses each work and then considers several breaches within the American feminist movement and how the plays reflect the issues of each conflict. The areas of contention within the feminist movement that are considered are: the strengths and shortcomings of liberal feminism, the most visible face of contemporary American feminism; whether pornography or its censorship is ultimately more harmful to women; how a binary division of gender, which can be understood as fundamental to the concept of feminism, is simultaneously oppressive; should feminists as a whole and within various racial, religious, and sexual subgroups attempt to find common ground or embrace the diversity of difference; how does the contemporary political rhetoric of family fit into a feminist vision; can there be a feminist style or is the search for one inherently essentialist; and, finally, how to account for the failure of the movement evident in the success of women who appear to imitate the work of male writers. The thesis concludes that feminist playwrights and their work, like the feminist movement itself must negotiate between efficacious unity and inclusive diversity. Similarly, plays that seek to alter the status quo must walk a fine line between transgression and commercial appeal. Each of the women considered navigates these paths differently, with diverse styles and goals.